PENGGUNAAN UPAH BAYANGAN UNTUK MEMPERKIRAKAN PENAWARAN TENAGA KERJA USAHATANI Kasus Pada Usahatani Ubikayu di Kabupaten Banyumas - INDAH WIDYARINI; SARDJU SUBAGYO (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2007)
Shadow wages can be used for estimation labor supply of farm household with Cobb-Douglas production function. The research conducted in five villages, i.e., Pageraji, Pejogol,Cilongok, Pernasidi, and Cikidang in Banyumas Regency. The respondents were chosen byCluster Random Sampling. The research result showed that the shadow wages as a supplyfunction of cassava farm in dry land were flatter then in paddy land. The more shadow wagesthe more labor supply.